A Cascade Suzuki–Miyaura/Diels–Alder Protocol: Exploring the Bifunctional Utility of Vinyl Bpin - Cain, David L.; McLaughlin, Calum; Molloy, John J.; Carpenter-Warren, Cameron; Anderson, Niall A.; Watson, Allan J. B. (Synlett, 2019)
Cascade reactions are an important strategy in reaction design, allowing streamlining of chemical synthesis. Here we report a cascade Suzuki–Miyaura/Diels–Alder reaction, employing vinyl Bpin as a bifunctional reagent in two distinct roles: as an organoboron nucleophile for cross-coupling and as a Diels–Alder dienophile. Merging these two reactions enables a rapid and operationally simple synthesis of functionalized carbocycles in good yield. The effect of the organoboron subtype on Diels–Alder regioselectivity was investigated and postsynthetic modifications were carried out on a model substrate. The potential for a complementary Heck/Diels–Alder process was also assessed.
Keywords: Bpin; cascade; cross-coupling; Diels–Alder; Suzuki–Miyaura